(untitled) (Applied Biological Research, 2023)
Plants with therapeutic value are still the only way forward for health care as their acceptance has grown all over the world. The information of the utilization of traditional medicinal plants in Kurdistan region is still at hand of the traditional herbalist. The study aimed at to identify different medicinal plants used by traditional herbalist in Choman locale of Erbil in Northern Iraq. Non-random probability sampling and expert method with the aid of a in-depth interview guide were used. Only plant species with a minimum of 0.5 relative frequency of citation were reported. Forty-one plants exhibiting medicinal properties have been documented. The family Asteraceae has highest abundance in the area. Allium sativum had highest used value (0.5). Leaves (32.7%) and fruits (23.6%) are the most utilized parts of medicinal plants in the study area. The most prepared form of preparation is decoction (45.5%) and direct form (30.9%). Oral is the most common application form (61.8%). People of Choman in Kurdistan region of Iraq have long been using medicinal plants for the treatment of various ailments like cold, cough, fever, diabetes. It is, therefore, necessary to conduct ethnobotanical studies in all the communities of Kurdistan region in Iraq.